Analisis Konsumsi Bahan Bakar Mesin Induk Pada Kapal Phinisi Natural 001 Untuk Perjalanan Wisata Taman Nasional Komodo - Nugraha, I Made Aditya; Pramana, Putu Indra; Luthfiani, Febi (Jurnal Sumberdaya Akuatik Indopasifik, 2023)
The operation of the engine on a ship is supported by sufficient fuel. Fuel is converted into mechanical energy to drive engines on the ship, such as the main engine and auxiliary engines. The Phinisi Natural 001 ship is one of the tourist ships that operates tourist services in the Komodo National Park Tourism area, so to support these activities it is necessary to have appropriate fuel requirements. There is a lack of information about the fuel requirements on this ship, so an analysis was carried out on the fuel consumption needs of the main engine on the Phinisi Natural 001 ship. This is important to be able to predict and prepare for fuel needs during tourist trips. Descriptive methods were used to support this activity, namely interview procedures, direct observation, regression analysis, work analysis and T Test. Based on the results obtained, significant differences were found between calculated and observed fuel consumption results on the 2D1N journey (p<0, 05), but in the 3D2N trip no significant differences were found (p>0.05). From the calculation results, the average amount of fuel used in the 2D1N and 3D2N travel programs was 95.31 liters and 146.66 liters, while the observation results obtained were 113.33 liters and 136.67 liters. The differences in the results of calculations and observations are caused by internal and external factors such as blockages in the nozzle, the ship floating, shipping routes, and weather influences, such as currents and sea waves during the trip.